2006
DOI: 10.1063/1.2226981
|View full text |Cite
|
Sign up to set email alerts
|

Wave mode conversion and mode transition in very high radio frequency helicon plasma

Abstract: In a very high radio frequency helicon plasma, experimental evidences for a wave mode conversion between the helicon mode and the Trivelpiece-Gould mode ͑TG mode͒ are presented. The helicon mode generation was detected when Ͻ ce / 2 was satisfied, and the helicon mode was converted to the TG mode at the plasma periphery below 140 G. As no more mode conversion to the TG mode occurs above 140 G, the plasma was directly heated by the helicon mode and a subsequent abrupt mode transition occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Yun et al have found a density rise near the LH frequency with m = 0 antennas [99]. Kim and Chang measured the ion energy distributions [100], and Eom et al [101][102][103] have generated helicons at high frequencies up to 180 MHz.…”
Section: Experiments By Othersmentioning
confidence: 99%
“…Yun et al have found a density rise near the LH frequency with m = 0 antennas [99]. Kim and Chang measured the ion energy distributions [100], and Eom et al [101][102][103] have generated helicons at high frequencies up to 180 MHz.…”
Section: Experiments By Othersmentioning
confidence: 99%